Evaluation of cytotoxic profile of hydroalcoholic extract of fruit rinds of Garcinia pedunculata on human embryonic kidney and breast carcinoma cells - Sharma, Sukrant; Mundugaru, Ravi; Dakappa, Pradeepa H.; Naik, Pundalik R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The fruit rinds of Garcinia pedunculata has potential medicinal properties and used in many chronic ailments. It has been demonstrated that cytoprotective effects in various experimental research works. But its cytotoxic effect has not been evaluated. The present study was aimed to screen its relative cytotoxic effect on normal and cancer cell lines. Methods: In the present study, the cytotoxic effect of hydro alcoholic extract of Garcinia pedunculata was evaluated on normal human embryonic kidney (HEK-293) and M.D. Anderson metastatic breast cancer cell lines (MDA-MB 231) using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results: Higher dose level of hydro alcoholic extract of Garcinia pedunculata (HAGP) (500 μg/ml) has shown considerable increase (112.503) in the percentage viability of HEK-29 whereas; there is a remarkable decrease in the viable cell population (77.490) in MDA-MB 231. Conclusions: Based on the observed results we could conclude that HAGP has potential cytotoxic effect on the cancer cell line without altering the normal cell growth and proliferation. Thus it has potential to develop as a safer chemotherapeutic agent. Further detailed exploration is required to confirm its therapeutic efficacy in different cancer cell lines.